(3GdUehO h GdJfGaS aj ehGLgI GdJMOjGJ GdYedjI (B:s (3GdGbJUGO GdGSJKeGQ , GdCef , GdeLJeY (B/s - (3HhdcSj, eGQLQjJ Ce(B.s; (3OGQ GdJQLeIs ((3HjQhJ(B: s (3GdOGQ GdYQHjI ddYdhe(B, s, 2009)
(3aj Xd HQjb fLeI NGaJI(B- (3CLRGA ef gfG hef gfGc(B- (3CgejI GdYbd(B- (3GdJacjQ GdeWdb(B- (3GdJeGS GdWQjb(B- (3ef Ybd Gdi Ybd(B- (3hYGO HQjb fLeJfG GdNGaJI(B.s
(3eQGLY U(B.165(3; ghGeT U(B.177s
Keywords: (3GdGSJKeGQs; (3GdGbJUGOs